PENGARUH PERFORMANCE-BASED BUDGETING DAN VALUE FOR MONEY TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN PENGENDALIAN AKUNTANSI SEBAGAI VARIABEL MODERASI - Try Sutriani; Haliah Haliah; Nirwana Nirwana (Jurnal Akuntansi dan Keuangan, 2022)
The purpose of this study is to examine the factors affecting the performance accountability of Makassar city government agencies by relaxing accounting controls. The research was conducted on OPD in Makassar city. The sort of studies used is quantitative. This study includes a population of 14 OPD and a total sample of 56 people using primary data collected through questionnaires. Data from this study were analyzed using analytical approaches with multiple regression analysis and Moderated Regression Analysis (MRA). The study describes accounting control as a moderating variable. This is because accounting controls can be used to assess the costs and profitability of certain successes and select the best alternatives and problem statements to increase accountability for the agency's financial performance. The study found a positive and significant effect between performance-based budgeting and value-for-money on agency performance accountability. Moderation regression analysis shows that control controls can facilitate performance-based budgeting and value-for-money (cost-effectiveness) in the accountability of an agency's performance.